Pengaruh Citra Merek terhadap Kepuasan Pasien di Instalasi Rawat Jalan Rumah Sakit Umum Asy Syifa Sambi Boyolali - Maharani Ahyunasaka; Anton Susanto; Hesty Latifa Noor (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The increase in the number of patient visits at Asy Syifa Sambi General Hospital was not accompanied by an increase in patient satisfaction. In fact, patient satisfaction actually decreased slightly, although it was still within the ideal category. This condition raises questions regarding the role of hospital image in influencing patient satisfaction. This study aims to determine the effect of brand image on patient satisfaction in the outpatient installation of Asy Syifa Sambi General Hospital, Boyolali. The type of research used was quantitative with a non-experimental design (analytical survey) and a cross-sectional approach. The number of samples in this study was 100 respondents obtained by non-probability sampling technique using the accidental sampling method. Data analysis was carried out through simple linear regression analysis. The results of the univariate analysis showed that the brand image variable was categorized as